Radiographic Imaging to Evaluate Food Passage Rate in Preterm Piglets as a Model for Preterm Infants - Kappel, Susanne Soendergaard; Sangild, Per Torp; Scheike, Thomas; Friborg, Christel Renée; Gormsen, Magdalena; Aunsholt, Lise (Frontiers in Pediatrics, 2021)
Objectives and study: Gut motility in infants mature with increasing post-menstrual age and is affected by numerous hormonal, immunological, and nutritional factors. However, it remains unclear how age and diet influence gut motility and its relation to feeding intolerance and gastric residuals in preterm neonates. Using preterm piglets as a model for infants, we investigated if contrast passage rate, as determined by X-ray contrast imaging, is affected by gestational age at birth, advancing postnatal age, and different milk diets. Methods: Contrast passage rate was evaluated using serial abdominal X-ray imaging on postnatal day 4 and 18 in preterm and near-term piglets fed infant formula, colostrum, or intact bovine milk, with or without added fortifier (total n=140). Results: Shortly after birth, preterm piglets had a faster small intestinal, and slower colon passage rate of contrast solution than near-term piglets (p<0.05, day 4). Among the preterm piglets, formula-fed animals showed a faster contrast passage rate to caecum, and through the colon region, than colostrum-fed pigs (both p<0.05, day 4). Shortly after birth, preterm pigs showed a slow passage rate through the stomach and colon regions compared with piglets beyond their neonatal adaptation phase (both p<0.05, between day 4 and 18). Adding a nutrient fortifier to dilute milk increased body growth, gastric residuals, intestinal length, and weight but did not affect any of the observed passage rates of contrast solution. Conclusion: Serial X-ray contrast imaging is a feasible method to assess food passage rate in preterm piglets. Contrast passage rate through different gut segments is affected by gestational age at birth, postnatal age, and milk diet. The preterm piglet could be a good model to investigate clinical and dietary factors that support the maturation of gut motility and thereby feeding tolerance and gut health in preterm infants.